The impact of fault seal analysis and Matruh canyon of the petroleum trapping for Alam El Bueib Member at Emry Oil Field, Western Desert, Egypt. - Essa, Ahmed A.; El-Hafez, Tharwat H. Abd; Salah, Salah S. (Iraqi Journal of Science, 2023)
This study aims to overcome the unexpected hydrocarbon non-potentiality detected in the upper Alam El-Bueib (I to IIIE) and justify the hydrocarbon accumulation within Alam El-Bueib (IIIG) at the Emry oil field, also, it is important to highlight the importance of fault seal analysis and the impact of Matruh canyon as a seal. Seismic interpretation and 3D structural framework are carried out using the fault-seal analysis technique for fault no.1 (F1). To assess the fault zone’s capacity to be defined as either seal or leakage. Litho-facies juxtaposition diagram (Allan diagram) and Shale Gouge Ratio (SGR) were generated. It is concluded that the possible reason for the dry reservoir of the upper part of Alam El Bueib (Alam El Bueib I to IIIE) due to the leakage of the fault (F1). On the other hand, the seal mechanism for Alam El Bueib IIIG is mainly related to increasing the thickness of the Matruh shale and Matruh Canyon act as a seal rock. SGR for Alam El Bueib IIIG is around 80%, which confirms the presence of the shale in Matruh Canyon is the reason for accumulating the hydrocarbon at Alam El Bueib IIIG.